The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1063/1.3527972
|View full text |Cite
|
Sign up to set email alerts
|

Molecular n-type doping for air-stable electron transport in vacuum-processed n-channel organic transistors

Abstract: The effects of n-type doping on the air-stability of vacuum-processed n-channel organic transistors have been investigated using perylene diimides and pyronin B as the active layer and dopant, respectively. Systematic studies on the influence of doping location revealed the n-type doping of bulk active layer or channel region significantly improves air-stability by compensating for the trapped electrons with the donated mobile electrons. Although n-type doping at the electrode contact could readily turn on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 23 publications
0
76
0
Order By: Relevance
“…Surprisingly, however, in contrast to inorganic semiconductors, doping also the channel of organic transistors still is more the exception than the rule and comparably few examples exist where molecularly doped channels were successfully employed in unipolar depletion-mode OFETs [90][91][92][93]. A typical setup for such a device is depicted in Figure 3c, where the authors employ …”
Section: Applications Employing Molecularly Doped Oscsmentioning
confidence: 95%
“…Surprisingly, however, in contrast to inorganic semiconductors, doping also the channel of organic transistors still is more the exception than the rule and comparably few examples exist where molecularly doped channels were successfully employed in unipolar depletion-mode OFETs [90][91][92][93]. A typical setup for such a device is depicted in Figure 3c, where the authors employ …”
Section: Applications Employing Molecularly Doped Oscsmentioning
confidence: 95%
“…[25][26][27] It has been reported that N-DBI doping can improve the air stability of n-channel organic field effect transistors. [25,28] 3-dimethyl-2-phenyl-2,3-dihydro-1H-benzoimidazole (N-DMBI) has also been used to n-dope phenyl-C 61 -butyric acid methyl ester in an inverted structure. [29] However, after film deposition, the dopant must be activated via overnight thermal annealing in an inert atmosphere after film deposition.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…Recently, the Bao group reported that OFET devices with N-DMBI doped PCBM [ 52 ] and pyronin B-doped perylene diimides [ 53 ] active layers show exceptional device stability in ambient conditions. Recently, the Bao group reported that OFET devices with N-DMBI doped PCBM [ 52 ] and pyronin B-doped perylene diimides [ 53 ] active layers show exceptional device stability in ambient conditions.…”
Section: Solar Cell Performancementioning
confidence: 99%